(untitled) (Herald of Journalism, 2016)
Impact of world mass media on political, economic and scientific and technical factors of society and national features in the sphere of communication became a basis of the new stage of political communication development. The article is dedicated to the analysis of common features and differences in various foreign countries experience in political communication development.